Pre-referral rectal artesunate to prevent death and disability in severe malaria: a placebo-controlled trial - Gomes, MF (Lancet Publishing Group, 2009)
BACKGROUND: Most malaria deaths occur in rural areas. Rapid progression from illness to death can be interrupted by prompt, effective medication. Antimalarial treatment cannot rescue terminally ill patients but could be effective if given earlier. If patients who cannot be treated orally are several hours from facilities for injections, rectal artesunate can be given before referral and acts rapidly on parasites. We investigated whether this intervention reduced mortality and permanent disability. METHODS: In Bangladesh, Ghana, and Tanzania, patients with suspected severe malaria who could not be treated orally were allocated randomly to a single artesunate (n=8954) or placebo (n=8872) suppository by taking the next numbered box, then referred to clinics at which injections could be given. Those with antimalarial injections or negative blood smears before randomisation were excluded, leaving 12 068 patients (6072 artesunate, 5996 placebo) for analysis. Primary endpoints were mortality, assessed 7–30 days later, and permanent disability, reassessed periodically. All investigators were masked to group assignment. Analysis was by intention to treat. This study is registered in all three countries, numbers ISRCTN83979018, 46343627, and 76987662. RESULTS: Mortality was 154 of 6072 artesunate versus 177 of 5996 placebo (2·5% vs 3·0%, p=0·1). Two versus 13 (0·03% vs 0·22%, p=0·0020) were permanently disabled; total dead or disabled: 156 versus 190 (2·6% vs 3·2%, p=0·0484). There was no reduction in early mortality (56 vs 51 deaths within 6 h; median 2 h). In patients reaching clinic within 6 h (median 3 h), pre-referral artesunate had no significant effect on death after 6 h or permanent disability (71/4450 [1·6%] vs 82/4426 [1·9%], risk ratio 0·86 [95% CI 0·63–1·18], p=0·35). In patients still not in clinic after more than 6 h, however, half were still not there after more than 15 h, and pre-referral rectal artesunate significantly reduced death or permanent disability (29/1566 [1·9%] vs 57/1519 [3·8%], risk ratio 0·49 [95% CI 0·32–0·77], p=0·0013). INTERPRETATION: If patients with severe malaria cannot be treated orally and access to injections will take several hours, a single inexpensive artesunate suppository at the time of referral substantially reduces the risk of death or permanent disability. FUNDING: UNICEF/UNDP/World Bank Special Programme for Research and Training in Tropical Diseases (WHO/TDR); WHO Global Malaria Programme (WHO/GMP); Sall Family Foundation; the European Union (QLRT-2000-01430); the UK Medical Research Council; USAID; Irish Aid; the Karolinska Institute; and the University of Oxford Clinical Trial Service Unit (CTSU).